PENDEKATAN DALAM MENGAJAR PERSPEKTIF SYAIFUL BAHRI DJAMARAH DAN ABUDDIN NATA. (Studi Komparatif Deskriftif) - Taufik Mukmin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
Teaching is not a light task for a teacher. In teaching teachers dealing with a group of students where they are sentient beings who need guidance and coaching to get to maturity. Students after experiencing the process of education and teaching are expected to become human beings who are self-aware of responsibility, self-employed, personable and moral. The result of this research is according to Syaiful Bahri Djamarah there are four component approach in teaching that is individual approach, group approach, mixed approach, educative approach. The opinion of Syaiful Bahri Djamarah is more general. Likewise, Abuddin Nata also argues that there are four components of the teaching approach: individual approach, group approach, mixed approach, educative approach, but the opinion of Abuddin Nata is more religious, this can be proved by the Qur'anic verses which is used as a guide in giving opinions.